Self-care interventions among the Jordanians during the COVID-19 lockdown: A cross-sectional study of community pharmacists’ observations - Isra Dmour, Khawla Dhamen Al-Hamaideh, Safa’a Ali Al-Qudah, Jumanah Dawood Al-Shawabkeh (Journal of Applied Pharmaceutical Science, 2023)
The COVID-19 pandemic demanded that many governments implement a comprehensive lockdown to control the spread of the disease. Several people sought self-care intervention practices to cope with this threat due to the lack of approved treatments or vaccines in the first year of the pandemic. Because hospitals and clinics were closed, community pharmacists were the first-line healthcare providers and reliable information sources. This study explores self-care measures among Jordanians during the repeated COVID-19 lockdowns. This study was conducted employing a self-administered online survey distributed to community pharmacies and medical representatives in various provinces of Jordan during the intermittent lockdown periods of the pandemic. According to the responses received from 138 participants, the elderly, chronic disease patients, and parents of young children were the major groups interested in purchasing self-care measures. Self-care measures included gloves, masks, alcohol-based disinfectants, and dietary supplements, with limited queries regarding antivirals and antimalarial drugs. The most reported sales regarding dietary supplements were vitamins B, C, and D, zinc, multivitamins, and many inquiries regarding herbs, mostly anise, lemon, garlic, ginger honey, and turmeric. In general, a decrease in sales was observed by most of the responding participants. Moreover, participants adhere to the continuous information published by the official health authorities. As frontline healthcare practitioners, community pharmacies need appropriate and mandatory training and continuous education to continue providing vital services in future pandemics.
Keywords: Self-care interventions, COVID-19, lockdown, pandemic, community pharmacists, dietary supplem